BIG DATA MARKET DEVELOPMENT PROSPECTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This paper discusses Big Data as a modern technological tool for the processing and storage of large volumes of data, which drives the development and automation of various economic processes. The main approaches and methods for working with Big Data, examples of using Big Data technologies, as well as trends in their development are examined.